Image Processing of Panoramic Dental X-Ray for Identifying Proximal Caries - Jufriadif Na'am; Johan Harlan; Sarifuddin Madenda; Eri Prasetyo Wibowo (Universitas Ahmad Dahlan, 2017)
This study aims to facilitate the identification of proximal caries in the Panoramic Dental X-Ray image. Twenty-seven X-Ray images of proximal caries were elaborated. The images in digital form were processed using Matlab and Multiple Morphological Gradient. The process produced sharper images and clarifies the edges of the objects in the images. This makes the characteristics of the proximal caries and the caries severity can be identified precisely.